The family remains : [large type] a novel - Jewell, Lisa (Thorndike Press large print core series., 2022)
"Early one morning, DCI Samuel Owusu is called to the scene of a gruesome discovery. When Owusu send the evidence for examination, he learns the bones are connected to a cold case that left three people dead thirty years ago. Rachel Rimmer has also received news that her husband, Michael, has been found dead in the cellar of his house in France. The French police her to come answer questions about Michael, that she very much doesn't want to answer. After fleeing London thirty years ago, Lucy Lamb is finally coming home. As they all race to discover answers to convoluted mysteries, they will come to find that they're connected in ways they could never have imagined"--